MODEL PENDAMPINGAN BIDAN DALAM TIM PEMBERDAYAAN KEHAMILAN (TPK) SEBAGAI UPAYA PROMOTIF DAN PREVENTIF UNTUK MENURUNKAN STUNTING DI DUSUN JOHO SENGKAN, CONDONGCATUR - Ratnaningsih, Dwi; Setyaningsih Sunardi, Kartika; Nugroho P, Haryo (Permata Indonesia, 2025)
Stunting and maternal mortality rate (MMR) are two major challenges in improving public health in Indonesia. One of the strategies developed is the formation of a Pregnancy Empowerment Team (TPK) involving midwives, cadres, and community leaders. This service aims to increase the capacity of TPK through a mentoring model by midwives in Joho Sengkan Hamlet, Condongcatur, Sleman. The implementation method includes local needs-based planning, two-day cadre training, and evaluation through pre-post tests and field observations. The results showed an increase in cadre knowledge by 30–35%, regular home visits by TPK, and increased family involvement in supporting pregnant women. This model has proven effective in strengthening the promotive and preventive functions of TPK, as well as strengthening the social role of cadres in the community. To maintain the sustainability of the program, long-term policy and funding support are needed.